Risk Assessment of Metal-Contaminated Soil Salt Consumption and Risk Management by Community Participation - Unwong, Pathanaporn; Mahaphon, Kanchana (Journal of Health Science of Thailand, 2017)
This study aimed to determine metal salt exposure and risk assessment on the consumption of soil salt contaminated with metals. Data were collected from interviews with 52 persons from 15 households who produced and consumed contaminated salts in Kuangnai Sub-district, Kuangnai district, Ubol Ratchathani province. Percentage, mean and standard deviation were used to analyze and calculate the amount of heavy metals including cadmium, lead, mercury and copper in the soil salt; and compared with the levels recommended in the provisional tolerable weekly intake (PTWI). It was found that the soil salt did contain metals in varying concentration; and the percentage of them when compared to the PTWI was 18.02, 35.12, 0.95, 1.34 and 18.79 for arsenic, lead, mercury, cadmium and copper, respectively, when calculated for an individual with an average weight of 55.33 kg. The daily consumption would be at higher percentage, considering that people also obtain the metals from other sources. There was also a concern of the risk for children and pregnant women. Since soil salt production has long been a source of income in addition to the value of local wisdom and culture, community participation activities were conducted to raise awareness on the possible risk as well as the identification of management approaches to continue making use of the salt field while avoiding health hazards to the people. The management zoning, product development, regular sampling for metal analysis and routine surveillance were recommended in order to address the health risk.